1999
DOI: 10.1289/ehp.99107s1145
|View full text |Cite
|
Sign up to set email alerts
|

Industrialization, electromagnetic fields, and breast cancer risk.

Abstract: The disparity between the rates of breast cancer in industrialized and less-industrialized regions has led to many hypotheses, including the theory that exposure to light-at-night and/or electromagnetic fields (EMF) may suppress melatonin and that reduced melatonin may increase the risk of breast cancer. In this comprehensive review we consider strengths and weaknesses of more than 35 residential and occupational epidemiologic studies that investigated the association between EMF and breast cancer. Although mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Although some earlier registry-based studies provided some support for a possible association between EMF exposure and female breast cancer (48), the most recent very large study, which incorporated exposure measurements in female workers, did not find an association (20b).…”
Section: Effects In Adultsmentioning
confidence: 97%
“…Although some earlier registry-based studies provided some support for a possible association between EMF exposure and female breast cancer (48), the most recent very large study, which incorporated exposure measurements in female workers, did not find an association (20b).…”
Section: Effects In Adultsmentioning
confidence: 97%
“…Extremely low frequency (ELF) occupational magnetic field (MF) exposure or proxy indicators of MF exposure (e.g., job titles, usual industry) have been reported to be associated with several cancer outcomes, including leukemia [Kheifets et al, 1997], brain cancer [Kheifets et al, 1995;Kheifets, 2001], and less frequently, female breast cancers [Loomis et al, 1994;Cantor et al, 1995;Coogan et al, 1996;Tynes et al, 1996;Feychting et al, 1998;Kheifets and Matkin, 1999;Forssen et al, 2000;Erren, 2001]. In addition, recent studies suggested possible associations of occupational MF exposure with noncancer endpoints such as Amyotrophic Lateral Sclerosis (ALS) [Davanipour et al, 1997;Johansen and Olsen, 1998;Savitz et al, 1998;Ahlbom, 2001] and Alzheimer's disease .…”
Section: Introductionmentioning
confidence: 99%
“…Although exposure to these agents might be encountered both in the general living environment and in occupational settings, epidemiologic studies of breast cancer and these exposures are quite limited. Occupational studies to date have found suggestive associations for breast cancer with organic solvents, polycyclic aromatic hydrocarbons (PAHs), selected pesticides, radiation, and electromagnetic fields [Goldberg and Labreche, 1996;Kheifets and Matkin, 1999] and specific occupation/industries, including nurses and physicians, teachers, managers, telephone and telegraph operators, and workers in the pharmaceutical, chemical, and textile industries [Hall and Rosenman, 1991;Bulbulyan et al, 1992;Rubin et al, 1993;Habel et al, 1995;Morton, 1995;Goldberg and Labreche, 1996;Coogan et al, 1996a;Calle et al, 1998;Petralia et al, 1998aPetralia et al, ,b, 1999Pollan and Gustavsson, 1999;Simpson et al, 1999;Band et al, 2000;Gardner et al, 2002;Zheng et al, 2002;Teitelbaum et al, 2003]. Results, however, have not been consistent and study limitations indicate the need for further studies in this area.…”
mentioning
confidence: 99%